ChemInform Abstract: Magnetization, Crystal Structure and Anisotropic Thermal Expansion of Single‐Crystal SrEr2O4. Issue 10 (March 2015) - Li, Hai‐Feng; Wildes, Andrew; Hou, Binyang; Zhang, Cong; Schmitz, Berthold; Meuffels, Paul; Roth, Georg; Brueckel, Thomas
Abstract A nearly stoichiometric Sr1.04Er2.09O4.00 single crystal is prepared according to previously published literature.